Numerical Study of the Unsteady Aerodynamics of Freely Falling Plates (Communications in Computational Physics, 2008)
The aerodynamics of freely falling objects is one of the most interestingflow mechanics problems. In a recent study, Andersen, Pesavento, and Wang [J. FluidMech., vol. 541, pp. 65-90 (2005)] presented the quantitative comparison between theexperimental measurement and numerical computation. The rich dynamical behavior,such as fluttering and tumbling motion, was analyzed. However, obvious discrepancies between the experimental measurement and numerical simulations still exist. Inthe current study, a similar numerical computation will be conducted using a newlydeveloped unified coordinate gas-kinetic method [J. Comput. Phys, vol. 222, pp. 155-175 (2007)]. In order to clarify some early conclusions, both elliptic and rectangularfalling plates will be studied. Under the experimental condition, the numerical solution shows that the averaged translational velocity for both rectangular and ellipticalplates are almost identical during the tumbling motion. However, the plate rotationdepends strongly on the shape of the plates. In this study, the details of fluid forcesand torques on the plates and plates movement trajectories will be presented and compared with the experimental measurements.